PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL BERBANTUAN MEDIA GAMBAR BERSERI UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV SD NEGERI 1 BEBALANG - Santhi K, Putu Agung Diah Ary; I Nengah Sueca; I Komang Nada Kusuma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine how the implementation of a contextual learning model supported by serial image media can improve the speaking skills of fourth-grade students at SD Negeri 1 Bebalang. The study employed the Classroom Action Research (CAR) method, conducted in four main stages: action planning, action implementation, observation and evaluation, and reflection. The research subjects were 26 fourth-grade students at SD Negeri 1 Bebalang. Data collection methods included observation and oral tests, utilizing observation sheets and assessment rubrics as instruments. Data analysis techniques comprised quantitative analysis for speaking skill test results and qualitative analysis for observation results. The research findings indicate that (1) the use of a contextual learning model supported by serial images improved the speaking abilities of fourth-grade students at SD Negeri 1 Bebalang through a structured, student-centered learning process, and (2) there was an increase in the average speaking skill score from 56.77 at the start of the study to 73.38 in the first cycle and 80.54 in the second cycle, with the classical mastery percentage rising from 19.23% to 57.69% and reaching 84.62% in the second cycle. Furthermore, improvements were observed across all speaking skill indicators, such as pronunciation, intonation, fluency, language use and content, as well as expression and body language.